1964
DOI: 10.1097/00006842-196407000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Allergic Potential and Psychopathology in Childhood Asthma

Abstract: A sample of 62 asthmatic children was divided into two subgroups on the basis of scores on the Allergic Potential Scale (APS)-an index of somatic or constitutional predisposition to allergy. The subgroups were compared, together with the associated mothers, on a variety of independent psychological tests and standardized interactional situations. The hypothesis that psychopathological factors would be observed significantly more often in the children identified by low APS scores, and their mothers, was support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1
2

Year Published

1966
1966
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 3 publications
(3 reference statements)
0
17
1
2
Order By: Relevance
“…Twenty-seven of them were sensitive to acetylsalicylic acid, and 28 were not. The authors sub-grouped the latter group into socalled atopic (13), infectious (9), and "mixed" (6).…”
Section: Biochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-seven of them were sensitive to acetylsalicylic acid, and 28 were not. The authors sub-grouped the latter group into socalled atopic (13), infectious (9), and "mixed" (6).…”
Section: Biochemistrymentioning
confidence: 99%
“…^ . ° Psychological aspects bronchial provocation testing one can also distinguish between different reaction types ( nality patterns have concerning asthma has There is the one type with immediate reac-been discussed in many papers (6,45,46,47). In tions and the one with slowly developing ob-this discussion a clear distinction has to be made struction.…”
Section: Immunological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of psychic factors in con nection with allergy in bronchial asthma was especially differentiated by Block et al [1964], who found more psychopathic signs in children (as well as their parents) with a lower allergic disposition than in those with a higher disposition to allergy. If the assump tion of Block et al that psychic components in allergic asthmatic patients are less impor tant were correct, then a higher disposition towards allergy would contraindicate psy chotherapeutic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that aller gic etiology alone, cannot completely explain the persistance of the asthma and suggest the possibility that psychological variables may help to explain the resid ual variance. The studies of Purcell (13), Block (2), McFadden (11) and others indicate that there is a subgroup of asthmatics, as high as 50 %, which is quite suggestible, essentially non-allergic, and in which emotions rank high among the précipitants of asthmatic attacks. This is the group which is likely to benefit most from the conjoint psychological management.…”
mentioning
confidence: 98%